2020
DOI: 10.3390/su12104040
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Banking Services’ Digitalization: The Practice of Diversification and Sustainable Development Goals

Abstract: The study aims to investigate threats that might occur in diversification management, operational risks of banking services in the process of digitalization, as well as the impact on customers and banks. The right choice of a risk management model for a bank plays an important role in the sustainable development of competitiveness and the transformation of banking activities in the future. This work assesses bank risks and determines information risks in relation to the total capital of Santander Bank of Spain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Effective risk management, including its diversification, is also ranked among the contributors to sustainable bank development in the global economy [46]. Examination of risk-mitigation strategies in Southeast Asia proved that the banks had become more sustainable when implementing viable risk-mitigation strategies [47].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Effective risk management, including its diversification, is also ranked among the contributors to sustainable bank development in the global economy [46]. Examination of risk-mitigation strategies in Southeast Asia proved that the banks had become more sustainable when implementing viable risk-mitigation strategies [47].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study focusing on single countries, such as Nigeria, shows that digitalization, if adequately implemented, has a positive impact on the performance of commercial banks [6], whereas a study in China showed that investment in digitalization contributes to sustainable production improvements in commercial banks [7]. On the other hand, the research reports that digitalization does not come free of operational risks [8] and that the digitization of banking poses a threat to several areas, including security [9]. Accordingly, innovation, willingness to take risks, and being ahead of competition should all be parts of successful digitalization [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, "democratization of credit" or "easy credit culture" has led to a significant increase in the share of the population accessing credit through various channels, registering the excessive indebtedness of certain categories of people, generally those with a low degree of financial education and low income earners. The widespread use of mobile phones by the population has also led to the emergence of specific financial services such as mobile banking, mobile payments, money transfers, and mobile international remittance services [19,27,[31][32][33]. So, financial inclusion is a complex process that is also fueled by the involvement of public authorities, financial institutions, IT companies that come up with solutions for the digitization and secure of financial services.…”
Section: Introductionmentioning
confidence: 99%